Clinicopathological Predictors of Response to Neoadjuvant Chemotherapy in Locally Advanced Breast Carcinoma: A Retrospective Study - Al Mamun, Iftakhar; Hossain, Md. Jahangir; Rahman, Mohammad Ziaur; Alam, Rana Jahangir; Islam, Md. Saiful; Faizi, . Sayem Al Monsur; Islam, Md. Saiful (Journal of Neonatal Surgery, 2024)
Background: Neoadjuvant chemotherapy (NACT) constitutes a fundamental component in the management of locally advanced breast carcinoma (LABC). The significant heterogeneity observed in treatment response underscores the imperative to identify reliable predictors to guide therapeutic personalization. Objective: This study sought to identify independent clinicopathological predictors of response to NACT in a cohort of patients with LABC. Methods: A retrospective, single-institution observational study was conducted involving 37 female patients with LABC who completed a full course of anthracycline-based NACT. Clinicopathological parameters were extracted from medical records. Pathological response was evaluated post-treatment, and patients were stratified into responders (achieving pathological complete or partial response) and non-responders (exhibiting stable or progressive disease). Univariate analyses and multivariate logistic regression were employed to ascertain independent predictors of treatment response. Results: The overall objective response rate was 72.9%, with a pathological complete response (pCR) rate of 24.3%. Univariate analysis indicated significant associations between treatment response and histological grade (p=0.05) and estrogen receptor (ER) status (p=0.01). Multivariate logistic regression confirmed ER positivity (Adjusted OR = 0.35; 95% CI: 0.08–0.91; p=0.03) and lower histological grade (Grade II vs. III, Adjusted OR = 0.42; 95% CI: 0.11–0.98; p=0.04) as independent predictors of a favourable response. The Ki-67 proliferation index, lymph node status, HER2 status, and chemotherapy regimen were not statistically significant in the multivariate model. Conclusion: This analysis identifies ER-positive status and lower histological grade as independent determinants of a favourable response to NACT in LABC. These findings elucidate the complex interplay between tumor biology and chemosensitivity, contributing to the evolving paradigm of tailored treatment strategies for this patient population